Plant-Derived Anti-inflammatory Agents: Molecular Pharmacology and Further Studies - Pelinescu, Diana Roxana (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Nature has represented and still represents a great pool of biologically active compounds and, at the same time, is a source of inspiration. In the first phase, the researchers turned their attention to the new compounds isolated from plants and their characterization in terms of their beneficial effects on human health. Recently, however, there have been extensive studies on the synthesis of compounds analogous to plant-derived compounds in order to prevent or treat diseases such as diabetes, obesity, chronic liver diseases, respiratory diseases, cardiovascular diseases, cancer, and so on. One of the mechanisms involved in the beneficial effect on human health is represented by plant-derived compounds' anti-inflammatory effects.